Innovative Method of Fuze Settings by a Number of OwnTurns of a Projectile - Grzegorz JĄCZEK (Nowatorska metoda programowania zapalników liczbą obrotów własnych pocisku, 2018)
This work presents a fuze setting method for ammunition for cannons and grenade launchers with a calibre of 25 to 40 mm, with a projectile body, that generates fragments by burst, on its trajectory during projectile flight. This setting method is based on fuze data delivery with a number of projectile turns between a muzzle and accurately predetermined point on its trajectory. The proposed method for fuzes setting is intended for precise determination of the distance travelled by the projectile, and should provide an alternative method for time setting fuzes. The method utilizes the phenomenon when the projectile, launched from the rifling barrel, overcomes a distance, in one turn path, equal to the barrel rifling pitch. This distance, independent of the projectile muzzle’s velocity and the number of turns made by the projectile, will determine the path travelled by it. In this work, important factors were presented, that apply to functioning the fuzes with spin detecting and turns counting features and that were omitted in descriptions of similar fuzes’ known solutions. These factors are: “idle gun elevation angles”, when signal is not generated; electromagnetic interferences, affecting quantity of impulses that are counted and random projectile initial orientation after a gun loading, in relation to projectile airbust point on a trajectory. Consideration of those important, from the ballistic point of view, factors in fuze construction makes it an innovative one. This publication shows also a proposition of the fuze electronic subassembly, that includes all of the questions that were mentioned.
Keywords: Programowanie zadziałania zapalników artyleryjskich